Night sky brightness monitoring network in Wuxi, China - Cui, Hengtao (J Quant Spectrosc Radiat Transf, 2021)
The rapid development of cities has brought tremendous pressure to astronomical observation, energy security, and the ecosystem. Automatic monitoring of night sky brightness (NSB) can help us to understand its regional differences and time variations of NSB effectively and to investigate the human and natural factors which lead to these changes. In this paper, the construction of Wuxi City night sky brightness monitoring network (WBMN) in China is presented. In addition to introducing the equipment and the installation of the network, a brief analysis of the data obtained from the stations will also be presented. The impact of human activities on the NSB is illustrated through its changes during the Spring Festival (lunar new year) and non-festival nights, and through a comparison study between NSB data taken from locations of different land usages. It is concluded that, while the reduction in human activities after non-festival midnights or the reduction in moon illumination near the new moon epoch led to darker night skies, brightening of the night skies may be attributed to firework displays during the nights of Spring Festival in 2019. On the other hand, the absence of firework during the Spring Festival in 2020 may explain the darker night skies. Finally, there is an evidence that the urban developments in Wuxi are degrading night sky quality.